Stakeholders, governance and responsibility - Seifi, Shahla; Crowther, David (Emerald Publishing Limited, 2018)
While it is generally accepted that both governance and corporate social responsibility are concerned with the way that an organisation manages its relations with its stakeholders, the actual relationships are not simple. The stakeholders who are considered to be dominant and most powerful can change dramatically over time. This is particularly so when governance or CSR is considered in the context of non-commercial forms of organisation. This book re-examines these relationships and the way in which they are changing and developing. The various contributions to the book address different aspects of these relationships from a wide international and interdisciplinary perspective.- Resumé vydavatel
Includes index.
Keywords: manažerská etika; řízení a správa společností; společenská odpovědnost firem; obchodní společnosti -- etické a morální aspekty; business ethics; corporate governance; corporate social responsibility; corporations -- ethical and moral aspects; elektronické knihy; sborníky; electronic books; papers of several authors